Active energy ray-curable adhesive composition and peel-off adhesive sheet

A solvent-free active energy ray-curable adhesive composition with (meth)acrylic resin and urethane (meth)acrylate addresses the challenge of residue-free peeling and adhesion in miniaturized workpieces, offering excellent adhesive properties and environmental benefits.

JP7600870B2Active Publication Date: 2024-12-17MITSUBISHI CHEM CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021090049
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-28
Publication Date
2024-12-17
Estimated Expiration
2041-05-28

AI Technical Summary

Technical Problem

Existing adhesive sheets used in protecting semiconductor wafers and other workpieces face challenges in achieving moderate adhesion without leaving residue, especially with the miniaturization and thinning of these components, and there is a need for solvent-free materials to reduce greenhouse gas emissions.

Method used

A solvent-free active energy ray-curable adhesive composition containing a (meth)acrylic resin and urethane (meth)acrylate with specific structural compatibility, which can be easily peeled off after irradiation with active energy rays, ensuring low adhesive strength and no residue.

Benefits of technology

The adhesive composition provides excellent adhesive properties before and after irradiation, with easy peelability and stain resistance, suitable for protecting workpieces like semiconductor wafers, printed circuit boards, and other materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600870000001
    Figure 0007600870000001
  • Figure 0007600870000002
    Figure 0007600870000002
  • Figure 0007600870000003
    Figure 0007600870000003
Patent Text Reader

Abstract

To provide an active energy ray-curable pressure-sensitive adhesive composition which is excellent in coating property, and is excellent in pressure-sensitive adhesive characteristics before and after irradiation with active energy rays, peelability and stain resistance after peeling when a pressure-sensitive adhesive layer of a peelable pressure-sensitive adhesive sheet is formed.SOLUTION: An active energy ray-curable pressure-sensitive adhesive composition is provided, contains at least an active energy ray-curable composition (X) containing a (meth)acrylic resin (A) and an active energy ray-curable compound (B), and satisfies all of the following requirements (α), (β) and (γ). Requirement (α): A solvent content in the active energy ray-curable composition (X) is less than 1 wt.%. Requirement (β): The active energy ray-curable compound (B) contains urethane (meth)acrylate (b). Requirement (γ): The urethane (meth)acrylate (b) has structure represented by general formula (1) and / or polyol-derived structure, and has three or more (meth)acryloyl groups in one molecule. General formula (1): -U-A. In the general formula (1), U represents an urethane bond, and A represents at least one selected from straight chain or branched alkyl, an alicyclic structure, an aromatic ring structure and heterocyclic structure.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an active energy ray-curable pressure-sensitive adhesive composition and a peel-off pressure-sensitive adhesive sheet, and more particularly to a peel-off pressure-sensitive adhesive sheet that is used for temporarily protecting workpieces such as semiconductor wafers, printed circuit boards, processed glass products, metal plates, plastic plates, etc. during processing and is then peeled off, and an active energy ray-curable pressure-sensitive adhesive composition that is suitably used for the pressure-sensitive adhesive layer of this peel-off pressure-sensitive adhesive sheet. [Background technology]

[0002] Conventionally, in processing steps such as fabricating integrated circuits on semiconductor wafers or drilling holes in them, protective adhesive sheets have been used to temporarily protect the workpiece, i.e., the semiconductor wafer, in order to prevent the workpiece from becoming dirty or damaged.

[0003] As adhesives used in such protective adhesive sheets, emulsion-type acrylic adhesives that are easily peeled off by heating have been proposed (see, for example, Patent Document 1). In addition, a UV-curable emulsion adhesive has been proposed that uses an acrylic emulsion polymerized without using an emulsifier (dispersant) and a urethane (meth)acrylate compound that has a self-emulsifying effect (see, for example, Patent Document 2). Furthermore, a pressure-sensitive adhesive sheet has been proposed that has a solventless acrylic pressure-sensitive adhesive layer containing an acrylic polymer, an acrylic monomer and a photopolymerization initiator on a substrate film (see, for example, Patent Document 3). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2013-201263 A [Patent Document 2] JP 2012-001615 A [Patent Document 3] JP 2004-269796 A Summary of the Invention [Problem to be solved by the invention]

[0005] The above-mentioned adhesive sheets are required to have an appropriate adhesive strength to the workpiece due to factors such as the miniaturization of processing techniques and the thinning of workpieces, but when they have completed their protective role and can be peeled off with extremely light force without leaving any glue behind. Furthermore, in recent years, greenhouse gas emissions have become a problem from the viewpoint of global environmental pollution. Therefore, attempts have been made to suppress the above problems by using water-based materials or solvent-free materials instead of conventional solvent-based materials.

[0006] However, the technique of Patent Document 1 has problems such as insufficient reduction in adhesive strength due to heating and the surfactant remaining on the wafer surface. On the other hand, in Patent Document 2, a self-emulsifying urethane (meth)acrylate is used to enable curing without using a surfactant, which solves the problem of the surfactant remaining on the wafer surface, but the adhesive strength after curing with active energy rays is insufficient, as in the technology of Patent Document 1. In addition, the adhesive sheet of Patent Document 3 is not an adhesive sheet that is easily peeled off by irradiation with active energy rays, and therefore cannot be applied to processed members that have been miniaturized or thinned.

[0007] Under such a background, the present invention aims to provide a solventless active energy ray-curable adhesive composition that can be suitably used for the adhesive layer of a peelable adhesive sheet, which has a melt viscosity suitable for hot melt coating, excellent compatibility between the (meth)acrylic resin (A) and the active energy ray-curable compound (B), and further has a desired adhesive strength before and after irradiation with active energy rays, and in particular has an adhesive property that the adhesive strength after irradiation with active energy rays is extremely low and can be peeled off without leaving any adhesive residue. Another object of the present invention is to provide a peelable adhesive sheet having an adhesive layer crosslinked with such an active energy ray-curable adhesive composition. [Means for solving the problem]

[0008] In general, when a solventless active energy ray-curable pressure-sensitive adhesive composition containing a (meth)acrylic resin and an active energy ray-curable compound is exposed to high temperatures, the thermal polymerization initiator remaining in the (meth)acrylic resin decomposes, causing the active energy ray-curable compound to start curing, and it is not even possible to heat the composition to the temperature required for hot melt coating. Therefore, the present inventors have found that, while using a solventless active energy ray-curable adhesive composition containing a (meth)acrylic resin (A) and an active energy ray-curable compound (B), the active energy ray-curable compound (B) contains a urethane (meth)acrylate (b), and the urethane (meth)acrylate (b) has a specific structure, thereby providing excellent compatibility with the (meth)acrylic resin (A). In addition, the present inventors have found that, as a result, a solventless active energy ray-curable adhesive composition can be obtained that has a melt viscosity suitable for hot melt coating, and that, when used as an adhesive for a peel-off adhesive sheet, has excellent adhesion properties before and after exposure to active energy rays and excellent contamination resistance after peeling.

[0009] That is, the present invention provides an active energy ray-curable pressure-sensitive adhesive composition that contains at least an active energy ray-curable composition (X) containing a (meth)acrylic resin (A) and an active energy ray-curable compound (B), and that satisfies all of the following requirements (α), (β), and (γ): Requirement (α): The content of the solvent in the active energy ray-curable composition (X) is less than 1% by weight. Requirement (β): The active energy ray-curable compound (B) contains a urethane (meth)acrylate (b). Requirement (γ): The urethane (meth)acrylate (b) has a structure represented by general formula (1) and / or a structure derived from a polyol, and has three or more (meth)acryloyl groups per molecule. -UA general formula (1) [U represents a urethane bond, and A represents at least one selected from a linear or branched alkyl group, an alicyclic structure, an aromatic ring structure, and a heterocyclic structure.]

[0010] The present invention also provides a peelable pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer in which the above-mentioned active energy ray-curable pressure-sensitive adhesive composition is crosslinked. Effect of the Invention

[0011] The active energy ray-curable pressure-sensitive adhesive composition of the present invention has excellent coatability, and when formed into a pressure-sensitive adhesive layer of a peel-type pressure-sensitive adhesive sheet, the pressure-sensitive adhesive layer can have excellent adhesive properties before and after irradiation with active energy rays, releasability, and contamination resistance after peeling. In the present invention, "peelability" refers to the degree of ease with which the peel-type pressure-sensitive adhesive sheet can be peeled off from an adherend after irradiation with active energy rays, and good peelability means that the adhesive strength upon peeling is small. In the present invention, "resistance to contamination" refers to the degree to which, when the peel-off pressure-sensitive adhesive sheet is peeled off from the adherend after irradiation with active energy rays, all or part of the adhesive of the peel-off pressure-sensitive adhesive sheet is unlikely to remain on the surface of the adherend, and good resistance to contamination means that almost none or part of the adhesive remains on the surface of the adherend. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, the embodiments of the present invention will be described in detail, but the present invention is not limited to these. In the present invention, "(meth)acrylic" means acrylic or methacrylic, "(meth)acryloyl" means acryloyl or methacryloyl, and "(meth)acrylate" means acrylate or methacrylate, respectively. In the present invention, the term "sheet" is not particularly differentiated from "film" or "tape" and is used to include these terms.

[0013] The active energy ray curable adhesive composition of the present invention is usually used to form an adhesive layer of a peelable adhesive sheet. The peelable adhesive sheet is premised on being attached to an adherend, for example, a workpiece such as a metal plate, a plastic plate, or a semiconductor wafer, and peeled off after being irradiated with active energy rays. The peelable adhesive sheet is formed by coating an active energy ray curable adhesive composition on a substrate sheet to form an adhesive layer, and after being attached to a workpiece, the adhesive layer is cured by irradiating with active energy rays, thereby reducing the adhesive strength, and the sheet can be easily peeled off from the workpiece.

[0014] Hereinafter, the active energy ray-curable pressure-sensitive adhesive composition of the present invention (hereinafter also simply referred to as "the pressure-sensitive adhesive composition of the present invention") contains at least an active energy ray-curable composition (X) containing a (meth)acrylic resin (A) and an active energy ray-curable compound (B). Each component will be explained in turn below.

[0015] [(Meth)acrylic resin (A)] The (meth)acrylic resin (A) is a resin obtained by polymerizing a polymerization component containing at least one kind of (meth)acrylic monomer, and examples thereof include (meth)acrylic resins obtained by polymerizing a polymerization component containing a (meth)acrylic monomer as a main component and, in some cases, various other polymerizable monomers. In the present invention, the (meth)acrylic resin (A) may be used alone or in combination of two or more kinds.

[0016] Incidentally, "containing a (meth)acrylic monomer as a main component" means that the (meth)acrylic monomer is contained in an amount of usually 40% by weight or more, preferably 50% by weight or more, and more preferably 60% by weight or more of the total polymerization components.

[0017] Examples of the (meth)acrylic monomer include (meth)acrylic acid or a derivative thereof, and (meth)acrylamide or a derivative thereof.

[0018] Examples of the derivatives of (meth)acrylic acid include alkyl group-containing (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, 2-methyl-2-nitropropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, n-pentyl (meth)acrylate, t-pentyl (meth)acrylate, 3-pentyl (meth)acrylate, 2,2-dimethylbutyl (meth)acrylate, n-hexyl (meth)acrylate, cetyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 4-methyl-2-propylpentyl (meth)acrylate, and n-octadecyl (meth)acrylate.

[0019] Other examples of the derivatives of (meth)acrylic acid include cycloalkyl (meth)acrylates such as cyclohexyl (meth)acrylate and cyclopentyl (meth)acrylate; aralkyl (meth)acrylates such as benzyl (meth)acrylate; biphenyloxy structure-containing (meth)acrylates such as biphenyloxyethyl (meth)acrylate; 2-isobornyl (meth)acrylate, 2-norbornylmethyl (meth)acrylate, 5-norbornen-2-yl-methyl (meth)acrylate, 3-methyl-2-norbornylmethyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and dicyclopentenyloxyethyl (meth)acrylate. polycyclic (meth)acrylates such as dicyclopentanyl (meth)acrylate; alkoxy group- or phenoxy group-containing (meth)acrylates such as 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-methoxymethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, methoxydiethylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, ethyl carbitol (meth)acrylate, phenoxyethyl (meth)acrylate, and alkylphenoxypolyethylene glycol (meth)acrylate; and the like.

[0020] Further, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate, hydroxyl group-containing (meth)acrylates such as [4-(hydroxymethyl)cyclohexyl]methyl acrylate, cyclohexanedimethanol mono(meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate, and epoxy group-containing (meth)acrylates such as glycidyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate glycidyl ether, are also included. Examples of the methacrylates include halogen-containing (meth)acrylates such as 2,2,2-trifluoroethyl (meth)acrylate, 2,2,2-trifluoroethylethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, hexafluoropropyl (meth)acrylate, octafluoropentyl (meth)acrylate, heptadecafluorodecyl (meth)acrylate, and 3-chloro-2-hydroxypropyl (meth)acrylate; alkylaminoalkyl (meth)acrylates such as dimethylaminoethyl (meth)acrylate; and oxetane group-containing (meth)acrylates such as 3-oxetanylmethyl (meth)acrylate, 3-methyl-oxetanylmethyl (meth)acrylate, 3-ethyl-oxetanylmethyl (meth)acrylate, 3-butyl-oxetanylmethyl (meth)acrylate, and 3-hexyl-oxetanylmethyl (meth)acrylate.

[0021] Examples of the (meth)acrylamide derivatives include N-alkyl group-containing (meth)acrylamide derivatives such as N-methyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-butyl(meth)acrylamide, and N-hexyl(meth)acrylamide; N-hydroxyalkyl group-containing (meth)acrylamide derivatives such as N-methylol(meth)acrylamide, N-hydroxyethyl(meth)acrylamide, and N-methylol-N-propane(meth)acrylamide; aminomethyl(meth)acrylamide; N-aminoalkyl group-containing (meth)acrylamide derivatives such as N-methoxymethyl(meth)acrylamide and N-ethoxymethyl(meth)acrylamide; N-mercaptoalkyl group-containing (meth)acrylamide derivatives such as mercaptomethyl(meth)acrylamide and mercaptoethyl(meth)acrylamide; and heterocycle-containing (meth)acrylamide derivatives such as N-acryloylmorpholine, N-acryloylpiperidine, N-methacryloylpiperidine, and N-acryloylpyrrolidine.

[0022] These (meth)acrylic monomers may be used alone or in combination of two or more. Among these (meth)acrylic monomers, alkyl group-containing (meth)acrylates are preferably used. The number of carbon atoms in the alkyl group in the alkyl group-containing (meth)acrylate is usually 1 to 20, preferably 4 to 18, and more preferably 8 to 12. Among them, n-butyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, and n-lauryl methacrylate are preferred because they have a glass transition temperature (Tg) of -30°C or less when a homopolymer is formed and can easily reduce the melt viscosity.

[0023] The polymerization components constituting the (meth)acrylic resin (A) may contain polymerizable monomers other than the (meth)acrylic monomers (hereinafter referred to as "other polymerizable monomers"). Examples of the other polymerizable monomers include unsaturated carboxylic acids such as crotonic acid, maleic acid, maleic anhydride, fumaric acid, citraconic acid, glutaconic acid, itaconic acid, acrylamido-N-glycolic acid, and cinnamic acid; carboxylic acid vinyl ester monomers such as vinyl acetate, vinyl propionate, vinyl stearate, and vinyl benzoate; aromatic ring-containing monomers such as styrene and α-methylstyrene; acrylonitrile, methacrylonitrile, vinyl chloride, vinylidene chloride, alkyl vinyl ethers, vinyl toluene, vinyl pyridine, vinyl pyrrolidone, itaconic acid dialkyl esters, fumaric acid dialkyl esters, allyl alcohol, acrylic chloride, methyl vinyl ketone, allyl trimethyl ammonium chloride, and dimethyl allyl vinyl ketone. These may be used alone or in combination of two or more.

[0024] The other polymerizable monomer may also contain a photocrosslinkable monomer, which generates radicals by the action of light. As the photocrosslinkable monomer, for example, a (meth)acrylate monomer having a benzophenone structure can be used. Specific examples thereof include 4-acryloyloxybenzophenone, 4-acryloyloxyethoxybenzophenone, 4-acryloyloxy-4'-methoxybenzophenone, 4-acryloyloxyethoxy-4'-methoxybenzophenone, 4-acryloyloxy-4'-bromobenzophenone, 4-acryloyloxyethoxy-4'-bromobenzophenone, 4-methacryloyloxybenzophenone, 4-methacryloyloxyethoxybenzophenone, 4-methacryloyloxy-4'-methoxybenzophenone, 4-methacryloyloxyethoxy-4'-methoxybenzophenone, 4-methacryloyloxy-4'-bromobenzophenone, 4-methacryloyloxyethoxy-4'-methoxybenzophenone, 4-methacryloyloxy-4'-bromobenzophenone, 4-methacryloyloxyethoxy-4'-bromobenzophenone, and mixtures thereof. By using such a photocrosslinkable monomer as a copolymerization component, a photocrosslinkable structural moiety can be formed in the (meth)acrylic resin (A).

[0025] The polymerization components constituting the (meth)acrylic resin (A) preferably contain an alkyl group-containing (meth)acrylate and a functional group-containing monomer. As such a functional group-containing monomer, it is preferable to contain at least one functional group-containing monomer selected from a hydroxyl group-containing monomer and a carboxyl group-containing monomer. Among these, a functional group-containing monomer containing a (meth)acryloyl group is preferable. Among these, a hydroxyl group-containing (meth)acrylate such as 2-hydroxyethyl (meth)acrylate and (meth)acrylic acid are particularly preferable.

[0026] The content of the alkyl group-containing (meth)acrylate is usually 40% by weight or more, preferably 50% by weight or more, and more preferably 60% by weight or more, based on the total weight of the polymer components constituting the (meth)acrylic resin (A). The upper limit is usually 100% by weight. The content of the functional group-containing monomer is preferably 0.1 to 40% by weight, more preferably 1 to 35% by weight, and particularly preferably 5 to 30% by weight, based on the total polymeric components constituting the (meth)acrylic resin (A). If the content of the functional group-containing monomer is too small, the cohesive force when the adhesive layer is formed tends to decrease, and the adhesive performance and peelability before curing with active energy rays tend to decrease. On the other hand, if the content is too large, the melt viscosity tends to increase and the pot life tends to be shortened.

[0027] The content of the other polymerizable monomers is usually 0 to 30% by weight, and preferably 0 to 20% by weight, based on the total weight of the polymerization components constituting the (meth)acrylic resin (A). Among the other polymerizable monomers, the content of the photocrosslinkable monomer is usually 0 to 10% by weight, preferably 0 to 5% by weight, based on the total polymerizable components constituting the (meth)acrylic resin (A).

[0028] [Method for producing (meth)acrylic resin (A)] The polymerization method for the (meth)acrylic resin (A) used in the present invention may be a conventionally known method such as solution (radical) polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc. For example, a method of mixing or dropping appropriately selected polymerization components and a thermal polymerization initiator into an organic solvent and polymerizing under predetermined polymerization conditions may be used. Among these, solution (radical) polymerization and bulk polymerization are preferred, and solution (radical) polymerization is particularly preferred in that a (meth)acrylic resin can be stably obtained.

[0029] A preferred method for producing the (meth)acrylic resin (A) used in the present invention will be described below, taking solution (radical) polymerization as an example. First, the above-mentioned copolymerization components and a thermal polymerization initiator are mixed or dropped into an organic solvent, and solution radical polymerization is carried out to obtain a (meth)acrylic resin solution.

[0030] (Organic solvent) Examples of organic solvents used in the polymerization reaction include aromatic hydrocarbons such as toluene and xylene; aliphatic hydrocarbons such as hexane; esters such as ethyl acetate and butyl acetate; aliphatic alcohols such as N-propyl alcohol and isopropyl alcohol; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone. These can be used alone or in combination of two or more. Among these solvents, it is preferable to use an organic solvent having a boiling point of 80° C. or less, in that the solvent can be distilled off from the (meth)acrylic resin solution obtained by solution polymerization to efficiently produce a solventless (meth)acrylic resin.

[0031] Examples of organic solvents having a boiling point of 80°C or lower include hydrocarbon solvents such as n-hexane (67°C); alcohol solvents such as methanol (65°C); ester solvents such as ethyl acetate (77°C) and methyl acetate (54°C); ketone solvents such as methyl ethyl ketone (80°C) and acetone (56°C); diethyl ether (35°C), methylene chloride (40°C), and tetrahydrofuran (66°C). Among these, in terms of versatility and safety, it is preferable to use ethyl acetate, acetone, and methyl acetate, and it is more preferable to use ethyl acetate and acetone. The numerical value in parentheses following the name of each of the organic solvents above is the boiling point of each of the organic solvents.

[0032] (Thermal polymerization initiator) As the thermal polymerization initiator used in the polymerization reaction, azo-based polymerization initiators and peroxide-based polymerization initiators, which are normal radical polymerization initiators, can be used. Examples of the azo-based polymerization initiator include 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobisisobutyronitrile, (1-phenylethyl)azodiphenylmethane, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-cyclopropylpropionitrile), and 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile). Examples of peroxide-based polymerization initiators include benzoyl peroxide, di-t-butyl peroxide, cumene hydroperoxide, lauroyl peroxide, t-butyl peroxypivalate, t-hexyl peroxypivalate, t-hexyl peroxyneodecanoate, diisopropyl peroxycarbonate, diisobutyryl peroxide, etc. These can be used alone or in combination of two or more kinds.

[0033] In the production of the (meth)acrylic resin, it is preferable to use an organic solvent having a boiling point of 80° C. or less as a reaction solvent for solution polymerization and carry out polymerization at a relatively low temperature, and if a thermal polymerization initiator having a high 10-hour half-life temperature is used in this case, the thermal polymerization initiator is likely to remain. If the thermal polymerization initiator remains, gelation tends to occur in the step of distilling off the solvent from the (meth)acrylic resin solution or in the step of heating the composition to form an active energy ray-curable pressure-sensitive adhesive composition, which will be described later.

[0034] Therefore, in the present invention, from the viewpoint of stably performing the step of distilling off the solvent from the (meth)acrylic resin solution obtained by solution polymerization and the step of heating to obtain an active energy ray-curable pressure-sensitive adhesive composition, it is preferable to use a thermal polymerization initiator having a 10-hour half-life temperature of 60°C or less among the above-mentioned thermal polymerization initiators. Among these thermal polymerization initiators, particularly preferred are 2,2'-azobis(2,4-dimethylvaleronitrile) (52°C), 2,2'-azobis(2-cyclopropylpropionitrile) (49.6°C), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) (30°C), t-butyl peroxypivalate (54.6°C), t-hexyl peroxypivalate (53.2°C), t-hexyl peroxyneodecanoate (44.5°C), diisopropyl peroxycarbonate (40.5°C), and diisobutyryl peroxide (32.7°C), and more preferred are 2,2'-azobis(2,4-dimethylvaleronitrile) (52°C) and t-hexyl peroxypivalate (53.2°C). The numbers in parentheses following each compound name above are the 10-hour half-life temperatures of each compound.

[0035] The amount of the thermal polymerization initiator used is usually 0.001 to 10 parts by weight, preferably 0.1 to 8 parts by weight, more preferably 0.5 to 6 parts by weight, particularly preferably 1 to 4 parts by weight, even more preferably 1.5 to 3 parts by weight, and especially preferably 2 to 2.5 parts by weight, based on 100 parts by weight of the polymerization components. If the amount of the thermal polymerization initiator used is too small, the polymerization rate of the (meth)acrylic resin tends to decrease, the amount of residual monomers tends to increase, and the weight average molecular weight of the (meth)acrylic resin tends to increase. If the amount used is too large, the time required for the follow-up heating described below tends to be long, and the production efficiency tends to decrease.

[0036] (Polymerization conditions, etc.) The polymerization conditions for the solution polymerization may be those known in the art. For example, the polymerization components and a thermal polymerization initiator may be mixed or dropped into a solvent, and polymerization may be carried out under predetermined polymerization conditions.

[0037] The polymerization temperature in the above polymerization reaction is usually 40 to 120° C., but in the present invention, from the viewpoint of stable reaction, it is preferably 50 to 90° C., more preferably 55 to 75° C., and particularly preferably 60 to 70° C. If the polymerization temperature is too high, the (meth)acrylic resin tends to be easily gelled, whereas if the polymerization temperature is too low, the activity of the thermal polymerization initiator decreases, so that the polymerization rate decreases and the amount of residual monomers tends to increase.

[0038] The polymerization time in the polymerization reaction (when the later-described follow-up heating is performed, the time until the start of the follow-up heating) is not particularly limited, but is preferably 0.5 hours or more from the last addition of the thermal polymerization initiator, more preferably 1 hour or more, particularly preferably 2 hours or more, and further preferably 5 hours or more. The upper limit of the polymerization time is usually 72 hours. The polymerization reaction is preferably carried out while refluxing the solvent in order to facilitate heat removal.

[0039] In the production of the (meth)acrylic resin, in order to reduce the amount of the remaining thermal polymerization initiator, it is preferable to thermally decompose the thermal polymerization initiator by follow-up heating. The above-mentioned drive-in heating temperature is preferably higher than the 10-hour half-life temperature of the above-mentioned thermal polymerization initiator, specifically, it is usually 40 to 150°C, and from the viewpoint of suppressing gelation, it is preferably 55 to 130°C, and more preferably 75 to 95°C. If the drive-in heating temperature is too high, the (meth)acrylic resin tends to turn yellow, and if it is too low, the polymerization components and thermal polymerization initiator remain, and the temporal stability and thermal stability of the (meth)acrylic resin tend to decrease. In this way, a (meth)acrylic resin solution can be obtained.

[0040] The (meth)acrylic resin used in the present invention is preferably a solvent-free (meth)acrylic resin that does not contain a solvent, and therefore it is preferable to subsequently distill off the solvent from the (meth)acrylic resin solution.

[0041] The step of distilling off the solvent from the (meth)acrylic resin solution can be carried out by a known method. Examples of the method of distilling off the solvent include a method of distilling off the solvent by heating and a method of distilling off the solvent by reducing pressure, but from the viewpoint of efficiently distilling off the solvent, a method of distilling off the solvent by heating under reduced pressure is preferred.

[0042] The temperature when distilling off the solvent by heating is preferably 60 to 150° C., and in particular, it is preferable to hold the reaction solution after polymerization of the (meth)acrylic resin at 60 to 80° C. to distill off the solvent, and then distill off the solvent at 80 to 150° C., in order to extremely reduce the amount of remaining solvent. Note that, in order to suppress gelation of the (meth)acrylic resin, it is preferable not to distill off the solvent at a temperature exceeding 150° C.

[0043] The pressure when the solvent is distilled off under reduced pressure is preferably 20 to 101.3 kPa, and in particular, it is preferable to maintain the pressure in the range of 50 to 101.3 kPa to distill off the solvent in the reaction solution, and then distill off the remaining solvent at 0 to 50 kPa, in order to extremely reduce the amount of remaining solvent. In this way, the (meth)acrylic resin (A) used in the present invention can be produced.

[0044] The content of the thermal polymerization initiator remaining in the (meth)acrylic resin (A) used in the present invention is usually preferably less than 400 ppm, more preferably less than 200 ppm, particularly preferably less than 100 ppm, and even more preferably less than 50 ppm. The lower limit is 0 ppm. If this value is too large, the thermal stability during coating tends to decrease. The content of the thermal polymerization initiator is measured by liquid chromatography-mass spectrometry (LC-MS). In order to adjust the amount of the remaining thermal polymerization initiator to the above amount, it is preferable to thermally decompose the thermal polymerization initiator by additional heating.

[0045] [Physical Properties of (Meth)acrylic Resin (A)] The weight average molecular weight (Mw) of the (meth)acrylic resin (A) obtained as described above is preferably 50,000 or more, more preferably 70,000 to 1,500,000, particularly preferably 90,000 to 1,000,000, and even more preferably 100,000 to 500,000. If the weight average molecular weight is too small, the cohesive force of the obtained pressure-sensitive adhesive layer decreases, and the adhesive performance and peelability before curing by active energy rays tend to decrease. If the weight average molecular weight is too large, the melt viscosity of the acrylic resin tends to increase, and the coatability tends to decrease.

[0046] The degree of dispersion of the (meth)acrylic resin (A) [weight average molecular weight (Mw) / number average molecular weight (Mn)] is preferably 10 or less, more preferably 7 or less. If the degree of dispersion is too high, the cohesive force tends to decrease. The lower limit of the degree of dispersion is usually 1.

[0047] The weight average molecular weight (Mw) of the (meth)acrylic resin (A) is the weight average molecular weight calculated based on the molecular weight of standard polystyrene. The weight average molecular weight was measured by a high performance liquid chromatography (manufactured by Japan Waters, "Waters2695 (main body)" and "Waters2414 (detector)") using a Shodex GPCKF-806L column (molecular weight exclusion limit: 2 × 10 7 , Separation range: 100~2×10 7The measurement can be performed by connecting three tubes in series (theoretical plate number: 10,000 plates / tube, filler material: styrene-divinylbenzene copolymer, filler particle size: 10 μm), and the number average molecular weight (Mn) can be measured in the same manner. The degree of dispersion can be determined from the measured values ​​of the weight average molecular weight (Mw) and number average molecular weight (Mn).

[0048] The melt viscosity of the (meth)acrylic resin (A) used in the present invention at 100° C. is usually less than 1000 Pa s, preferably 0.1 to 800 Pa s, and more preferably 1 to 500 Pa s. If this value is too small, the cohesive force when the adhesive layer is formed decreases, and the adhesive performance and peelability before curing with active energy rays tend to decrease. The melt viscosity at 100° C. is measured by a B-type rotational viscometer.

[0049] The glass transition temperature (Tg) of the (meth)acrylic resin (A) is preferably 20° C. or lower, more preferably −70° C. to 0° C., particularly preferably −68° C. to −10° C., and even more preferably −65° C. to −30° C. If the glass transition temperature is too low, the cohesive force when the adhesive layer is formed tends to decrease, and the adhesive performance and peelability before curing with active energy rays tend to decrease. If the glass transition temperature is too high, the melt viscosity of the active energy ray-curable adhesive composition tends to increase, and the coatability tends to decrease.

[0050] The glass transition temperature is calculated by the following Fox formula.

number

[0051] That is, the glass transition temperature (Tg) of the (meth)acrylic resin (A) is a value calculated by applying the glass transition temperature and weight fraction when a homopolymer is formed from each monomer constituting the (meth)acrylic resin (A) to the Fox equation. The glass transition temperature when a homopolymer is formed from each monomer constituting the (meth)acrylic resin (A) is usually measured by a differential scanning calorimeter (DSC) and can be measured by a method in accordance with JIS K7121-1987 or JIS K6240.

[0052] The refractive index of the (meth)acrylic resin (A) is usually 1.440 to 1.600. It is preferable to reduce the difference in refractive index between the (meth)acrylic resin (A) and the member to be laminated therewith, since this reduces optical loss at the interface between the members. The refractive index is a value measured by a thin film obtained from the (meth)acrylic resin (A) using a refractive index measuring device (Abbe refractometer 1T manufactured by Atago Co., Ltd.) at 23° C. using NaD rays.

[0053] The solvent content in the (meth)acrylic resin (A) is preferably less than 1% by weight, more preferably 0.5% by weight or less, and particularly preferably 0.1% by weight or less. If the content is too high, the cohesive strength of the resulting adhesive layer decreases, and the adhesive performance and peelability before curing with active energy rays tend to decrease. The solvent content was measured by gas chromatography-mass spectrometry (GC-MS).

[0054] [Active energy ray-curable compound (B)] The active energy ray-curable compound (B) used in the present invention contains a urethane (meth)acrylate (b). The urethane (meth)acrylate (b) has a structure represented by general formula (1) and / or a structure derived from a polyol. -UA general formula (1) [U represents a urethane bond (-NHCOO-), and A represents at least one selected from a linear or branched alkyl group, an alicyclic structure, an aromatic ring structure, and a heterocyclic structure.]

[0055] In the present invention, the urethane (meth)acrylate (b) is preferably a urethane (meth)acrylate compound (b-1) which is a reaction product of a hydroxyl group-containing (meth)acrylate compound (b1), a polyvalent isocyanate compound (b2), and a polyol compound (b3), or a urethane (meth)acrylate compound (b-2) which is a reaction product of a hydroxyl group-containing (meth)acrylate compound (b1), a polyvalent isocyanate compound (b2), a monool (b4), and, if necessary, a polyol compound (b3), in terms of compatibility with the (meth)acrylic resin (A) and releasability and contamination resistance after irradiation with active energy rays. In the present invention, the urethane (meth)acrylate compound (b) may be used alone or in combination of two or more kinds. The urethane (meth)acrylate (b) obtained by using the polyol compound (b3) has at least a structure derived from a polyol.

[0056] The reaction molar ratio of each component when synthesizing the urethane (meth)acrylate compound (b) will be described taking as an example a case in which the hydroxyl group-containing (meth)acrylate compound (b1) has one hydroxyl group, the polyvalent isocyanate compound (b2) has two isocyanate groups, the polyol compound (b3) has two hydroxyl groups, and the monool (b4) has one hydroxyl group. In the urethane (meth)acrylate compound (b-1), the reaction molar ratio of the hydroxyl group-containing (meth)acrylate compound (b1), the polyisocyanate compound (b2) and the polyol compound (b3) is usually about 2:1:2, i.e., polyisocyanate compound (b2):polyol compound (b3):hydroxyl group-containing (meth)acrylate compound (b1). In addition, the reaction molar ratio of the urethane (meth)acrylate compound (b-2), the hydroxyl group-containing (meth)acrylate compound (b1), the polyisocyanate compound (b2) and the monol (b4) is usually about 1:1:1, i.e., polyisocyanate compound (b2): hydroxyl group-containing (meth)acrylate compound (b1): monol (b4), and when a polyol compound (b3) is used in combination, the reaction molar ratio is usually about 2:1:1:1, i.e., polyisocyanate compound (b2): polyol compound (b3): ​​hydroxyl group-containing (meth)acrylate compound (b1): monol (b4).

[0057] The hydroxyl group-containing (meth)acrylate compound (b1) is preferably one having one hydroxyl group, and examples thereof include 2-hydroxyethyl acryloyl phosphate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, caprolactone-modified 2-hydroxyethyl (meth)acrylate, dipropylene glycol (meth)acrylate, fatty acid-modified glycidyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, 2-hydroxyethyl acrylate, di ... Examples of the hydroxyalkyl (meth)acrylate include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and the like. Further examples include hydroxyl group-containing (meth)acrylate compounds containing two ethylenically unsaturated groups, such as glycerin di(meth)acrylate and 2-hydroxy-3-acryloyl-oxypropyl methacrylate; and hydroxyl group-containing (meth)acrylate compounds containing three or more ethylenically unsaturated groups, such as pentaerythritol tri(meth)acrylate, caprolactone-modified pentaerythritol tri(meth)acrylate, ethylene oxide-modified pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, caprolactone-modified dipentaerythritol penta(meth)acrylate, and ethylene oxide-modified dipentaerythritol penta(meth)acrylate. These hydroxyl group-containing (meth)acrylate compounds (b1) can be used alone or in combination of two or more.

[0058] As the hydroxyl group-containing (meth)acrylate compound (b1), a hydroxyl group-containing (meth)acrylate compound containing three or more ethylenically unsaturated groups is preferred from the viewpoint of excellent reactivity and versatility, and pentaerythritol tri(meth)acrylate and dipentaerythritol penta(meth)acrylate are particularly preferred. In other words, the urethane (meth)acrylate (b) preferably has three or more (meth)acryloyl groups per molecule.

[0059] Examples of the polyisocyanate compound (b2) include aromatic polyisocyanates such as tolylene diisocyanate, diphenylmethane diisocyanate, polyphenylmethane polyisocyanate, modified diphenylmethane diisocyanate, xylylene diisocyanate, tetramethylxylylene diisocyanate, phenylene diisocyanate, and naphthalene diisocyanate; aliphatic polyisocyanates such as hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, lysine diisocyanate, and lysine triisocyanate; hydrogenated diphenyl diisocyanates such as phenyl diisocyanate, phenyl diisocyanate, and naphthalene diisocyanate; Examples of such polyisocyanates include alicyclic polyisocyanates such as dicyclohexylmethane diisocyanate (dicyclohexylmethane 4,4'-diisocyanate, etc.), hydrogenated xylylene diisocyanate, isophorone diisocyanate, and norbornene diisocyanate; isocyanurates or polymeric compounds of these polyisocyanates; allophanate-type polyisocyanates; biuret-type polyisocyanates; and water-dispersible polyisocyanates (for example, "Aquanate 100", "Aquanate 110", "Aquanate 200", "Aquanate 210", etc., manufactured by Nippon Polyurethane Industry Co., Ltd.).

[0060] Among these, in terms of excellent reactivity and versatility, aliphatic diisocyanates such as hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, and lysine diisocyanate; and alicyclic diisocyanates such as hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, and norbornene diisocyanate are preferred, with isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, and hexamethylene diisocyanate being more preferred, and isophorone diisocyanate and hydrogenated diphenylmethane diisocyanate being particularly preferred.

[0061] The polyol-based compound (b3) may be any compound containing two or more hydroxyl groups, such as aliphatic polyols, alicyclic polyols, polyether polyols, polyester polyols, polycarbonate polyols, polyolefin polyols, polybutadiene polyols, polyisoprene polyols, (meth)acrylic polyols, polysiloxane polyols, etc. These polyol-based compounds (b3) may be used alone or in combination of two or more.

[0062] Examples of the aliphatic polyols include ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, trimethylene glycol, dimethylolpropane, neopentyl glycol, 2,2-diethyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,4-tetramethylenediol, 1,3-tetramethylenediol, 2-methyl-1,3-trimethylenediol, 1,5-pentamethylenediol, 1, Examples of the alcohols include aliphatic alcohols containing two hydroxyl groups, such as 6-hexamethylenediol, 3-methyl-1,5-pentamethylenediol, 2,4-diethyl-1,5-pentamethylenediol, pentaerythritol diacrylate, 1,9-nonanediol, and 2-methyl-1,8-octanediol; sugar alcohols, such as xylitol and sorbitol; and aliphatic alcohols containing three or more hydroxyl groups, such as glycerin, trimethylolpropane, and trimethylolethane.

[0063] Examples of the alicyclic polyol include cyclohexanediols such as 1,4-cyclohexanediol and cyclohexyldimethanol; hydrogenated bisphenols such as hydrogenated bisphenol A; and tricyclodecane dimethanol.

[0064] Examples of the polyether polyol include polyalkylene glycols such as polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polybutylene glycol, polypentamethylene glycol, and polyhexamethylene glycol, and random or block copolymers of these polyalkylene glycols.

[0065] Examples of the polyester polyol include a condensation polymer of a polyhydric alcohol and a polycarboxylic acid; a ring-opening polymer of a cyclic ester (lactone); and a reaction product of three components, a polyhydric alcohol, a polycarboxylic acid, and a cyclic ester. Examples of the polyhydric alcohol include ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, trimethylene glycol, 1,4-tetramethylene diol, 1,3-tetramethylene diol, 2-methyl-1,3-trimethylene diol, 1,5-pentamethylene diol, neopentyl glycol, 1,6-hexamethylene diol, 3-methyl-1,5-pentamethylene diol, 2,4-diethyl-1,5-pentamethylene diol, glycerin, trimethylolpropane, trimethylolethane, cyclohexanediols (such as 1,4-cyclohexanediol), bisphenols (such as bisphenol A), and sugar alcohols (such as xylitol and sorbitol). Examples of the polyvalent carboxylic acid include aliphatic dicarboxylic acids such as malonic acid, maleic acid, fumaric acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, and dodecanedioic acid; alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid; and aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, orthophthalic acid, 2,6-naphthalenedicarboxylic acid, paraphenylenedicarboxylic acid, and trimellitic acid. Examples of the cyclic ester include propiolactone, β-methyl-δ-valerolactone, and ε-caprolactone.

[0066] Examples of the polycarbonate-based polyol include a reaction product of a polyhydric alcohol with phosgene; a ring-opening polymer of a cyclic carbonate (such as an alkylene carbonate); and the like. The polyhydric alcohols include those exemplified in the description of the polyester polyols, and the alkylene carbonates include, for example, ethylene carbonate, trimethylene carbonate, tetramethylene carbonate, hexamethylene carbonate, and the like. The polycarbonate-based polyol may be any compound having a carbonate bond in the molecule and a hydroxyl group at the end, and may have an ester bond in addition to the carbonate bond.

[0067] The polyolefin polyols include those having a homopolymer or copolymer of ethylene, propylene, butene, or the like as a saturated hydrocarbon skeleton and having hydroxyl groups at the molecular terminals.

[0068] The polybutadiene-based polyol may be a polybutadiene polyol having a butadiene copolymer as a hydrocarbon skeleton and having hydroxyl groups at the molecular terminals. The polybutadiene-based polyol may be a hydrogenated polybutadiene polyol in which all or a part of the ethylenically unsaturated groups contained in the structure are hydrogenated.

[0069] The polyisoprene-based polyol may be a polyisoprene polyol having a copolymer of isoprene as a hydrocarbon skeleton and having hydroxyl groups at the molecular terminals. The polyisoprene-based polyol may be a hydrogenated polyisoprene polyol in which all or a part of the ethylenically unsaturated groups contained in the structure are hydrogenated.

[0070] The (meth)acrylic polyol may be one having at least two hydroxyl groups in the molecule of a (meth)acrylic acid ester polymer or copolymer. Examples of such (meth)acrylic acid ester include (meth)acrylic acid alkyl esters such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, and octadecyl (meth)acrylate.

[0071] Examples of the polysiloxane polyol include dimethylpolysiloxane polyol and methylphenylpolysiloxane polyol.

[0072] Among these, from the viewpoint of cost, aliphatic polyols and alicyclic polyols are preferably used, and from the viewpoint of versatility, polyether polyols, polyester polyols and polycarbonate polyols are preferably used.

[0073] The weight average molecular weight of the polyol-based compound (b3) is preferably 60 to 10,000, more preferably 100 to 5,000, and particularly preferably 200 to 4,000. If the weight average molecular weight of the polyol-based compound (b3) is too large, the resulting urethane (meth)acrylate (b) and the (meth)acrylic resin (A) tend to be difficult to mix uniformly, and the peelability after irradiation with active energy rays tends to decrease. If the weight average molecular weight of the polyol-based compound (b3) is too small, cracks tend to easily occur in the pressure-sensitive adhesive layer after irradiation with active energy rays. The weight average molecular weight of the polyol compound (b3) is measured in the same manner as the weight average molecular weight (Mw) of the (meth)acrylic resin (A).

[0074] Examples of the monool (b4) include aliphatic monool, aromatic monool, alicyclic monool, polyoxyalkylene glycol monoalkyl ether, etc. The monool (b4) may be used alone or in combination of two or more kinds. Examples of the aliphatic monool include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, 1-pentanol, 1-hexanol, 2-methyl-1-pentanol, 4-methyl-2-pentanol, 2-ethyl-1-butanol, 1-heptanol, 1-octanol, 2-octanol, 1-nonanol, 1-decanol, 1-undecanol, 1-dodecanol, 1-hexadecanol, 1-heptadecanol, and 1-octadecanol. linear saturated aliphatic monools such as 1-oleyl alcohol, etc.; linear unsaturated aliphatic monools such as 1-oleyl alcohol, etc.; branched saturated aliphatic monools such as 2-ethylhexanol, 2-hexyldecanol, isooctadecanol, 3,5-dimethyl-1-hexanol, 2,2,4-trimethyl-1-pentanol, 2,6-dimethyl-4-heptanol, etc.; and the like. Examples of the aromatic monool include phenol, cresol, and benzyl alcohol. Examples of the alicyclic monool include cyclohexanol and methylcyclohexanol. Examples of the polyoxyalkylene glycol monoalkyl ether include reaction products of the above-mentioned aliphatic monools with polyoxypropylene glycol. Specific examples thereof include polyoxypropylene methyl ether, polyoxypropylene ethyl ether, polyoxypropylene butyl ether, polyoxypropylene-2-ethylhexyl ether, polyoxypropylene oleyl ether, and polyoxypropylene-2-octyldodecaether. From the viewpoint of versatility, the monool (b4) is preferably a linear or branched alkyl-containing alcohol having 1 to 36 carbon atoms, and more preferably a linear or branched alkyl-containing alcohol having 4 to 18 carbon atoms. These mono-ols (b4) can be used alone or in combination of two or more. By using a monool (b4) having at least one selected from a linear or branched alkyl group, an alicyclic structure, an aromatic ring structure, and a heterocyclic structure, a urethane (meth)acrylate (b) in which A in the general formula (1) has at least one selected from a linear or branched alkyl group, an alicyclic structure, an aromatic ring structure, and a heterocyclic structure is obtained.

[0075] The urethane (meth)acrylate compound (b) can be produced by reacting the above-mentioned components by known reaction means. An example of each of the compounds (b-1) and (b-2) will be shown below. (1) In the case of obtaining a urethane (meth)acrylate compound (b-1) A method of subjecting the above-mentioned hydroxyl group-containing (meth)acrylate compound (b1), a polyvalent isocyanate compound (b2), and a polyol compound (b3) to a urethane reaction. (2) In the case of obtaining a urethane (meth)acrylate compound (b-2) A method of subjecting the above-mentioned hydroxyl group-containing (meth)acrylate compound (b1), a polyisocyanate compound (b2), a monool (b4), and, if necessary, a polyol compound (b3) to a urethane reaction. The above urethane-forming reaction can be carried out by charging the above components into a reactor all at once or separately and by using a known reaction means. In addition, when producing a urethane (meth)acrylate-based compound (b-1), a method in which a polyol-based compound (b3) is reacted with a polyvalent isocyanate-based compound (b2) in advance to obtain a reaction product, and then the reaction product is reacted with a hydroxyl group-containing (meth)acrylate-based compound (b1) is useful in terms of the stability of the urethane-forming reaction and the reduction of by-products. For the same reason, when a urethane (meth)acrylate compound (b-2) is produced using a polyol compound (b3), a method is useful in which the polyol compound (b3) is reacted in advance with a polyisocyanate compound (b2), and the resulting reaction product is then reacted with a hydroxyl group-containing (meth)acrylate compound (b1) and a monool (b4).

[0076] In the reaction between the hydroxyl group-containing (meth)acrylate compound (b1) and the polyvalent isocyanate compound (b2), it is preferable to use a reaction catalyst for the purpose of promoting the reaction. Examples of such reaction catalysts include organometallic compounds such as dibutyltin dilaurate, trimethyltin hydroxide, and tetra-n-butyltin; metal salts such as zinc octenate, tin octenate, tin octylate, cobalt naphthenate, stannous chloride, and stannic chloride; triethylamine, benzyldiethylamine, 1,4-diazabicyclo[2,2,2]octane, 1,8-diazabicyclo[5,4,0]undecene, N,N,N',N' amine-based catalysts such as tetramethyl-1,3-butanediamine and N-ethylmorpholine; inorganic bismuth compounds such as bismuth nitrate, bismuth bromide, bismuth iodide and bismuth sulfide; organic bismuth compounds such as dibutyl bismuth dilaurate and dioctyl bismuth dilaurate; bismuth catalysts such as organic acid bismuth salts such as bismuth 2-ethylhexanoate, bismuth naphthenate, bismuth isodecanoate, bismuth neodecanoate, bismuth laurate, bismuth maleate, bismuth stearate, bismuth oleate, bismuth linoleate, bismuth acetate, bismuth bisneodecanoate, bismuth disalicylate and bismuth digallate; zirconium catalysts such as inorganic zirconium, organic zirconium and zirconium alone; and combinations of two or more catalysts such as zinc 2-ethylhexanoate / zirconium tetraacetylacetonate. Among these, dibutyltin dilaurate and organic bismuth compounds are preferred. These catalysts can be used alone or in combination of two or more.

[0077] In the above urethanization reaction, organic solvents that do not have a functional group that reacts with an isocyanate group, for example, esters such as ethyl acetate and butyl acetate; ketones such as methyl ethyl ketone and methyl isobutyl ketone; aromatics such as toluene and xylene, etc., can be used.

[0078] The reaction temperature for the urethane-forming reaction is usually 30 to 90° C., and preferably 40 to 80° C., and the reaction time is usually 2 to 10 hours, and preferably 3 to 8 hours.

[0079] The above urethanization reaction is preferably terminated when the residual isocyanate group content in the reaction system becomes 0.5% by weight or less, whereby the urethane (meth)acrylate compound (b) can be efficiently obtained.

[0080] The (meth)acryloyl group concentration of the urethane (meth)acrylate compound (b) thus obtained is usually 0.5 mmol / g or more, preferably 1 to 35 mmol / g, more preferably 1.5 to 20 mmol / g, and particularly preferably 2 to 15 mmol / g. By setting the (meth)acryloyl group concentration of the urethane (meth)acrylate compound (b) within the above range, it is possible to obtain a compound having excellent peelability after irradiation with active energy rays.

[0081] In addition, the urethane (meth)acrylate compound (b) preferably has three or more (meth)acryloyl groups from the viewpoint of releasability after irradiation with active energy rays. If the number of (meth)acryloyl groups is too small, sufficient crosslinking density cannot be obtained, and the releasability after irradiation with active energy rays tends to decrease.

[0082] The weight average molecular weight of the urethane (meth)acrylate compound (b) is usually 200 to 10,000, preferably 400 to 5,000, and more preferably 600 to 4,000. If the weight average molecular weight is too large, the active energy ray curable compound (B) and the (meth)acrylic resin (A) are difficult to mix uniformly, and the adhesive properties before and after irradiation with active energy rays tend to decrease. If the weight average molecular weight is too small, the cohesive force of the adhesive layer decreases, and the adhesive performance and peelability before curing with active energy rays tend to decrease.

[0083] The weight-average molecular weights mentioned above are those calculated based on the molecular weight of standard polystyrene. The samples were analyzed using a high-performance liquid chromatograph (manufactured by Japan Waters, "Waters 2695 (main unit)" and "Waters 2414 (detector)") with a Shodex GPC KF-806L column (molecular weight exclusion limit: 2×10 7 , Separation range: 100~2×10 7 The measurement is performed using three columns in series (theoretical plate number: 10,000 plates / column, filler material: styrene-divinylbenzene copolymer, filler particle size: 10 μm).

[0084] The viscosity of the urethane (meth)acrylate compound (b) used in the present invention at 60°C is preferably 50 to 10,000 mPa·s, more preferably 100 to 7,000 mPa·s, and particularly preferably 200 to 4,000. If the viscosity is too low, the cohesive force tends to decrease, and if it is too high, the coatability tends to decrease. The viscosity can be measured by an E-type viscometer.

[0085] The active energy ray-curable compound (B) used in the present invention may contain, as a constituent component, a monofunctional (meth)acrylate or a polyfunctional (meth)acrylate in addition to the urethane (meth)acrylate-based compound (b).

[0086] [Monofunctional (meth)acrylate] Examples of such monofunctional (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, acrylonitrile, 2-methoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, phenoxyethyl (meth)acrylate, 2-phenoxy-2-hydroxypropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, glycerin mono(meth)acrylate, glycidyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, tricyclodecanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and the like. peroxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, (2-methyl-2-ethyl-1,3-dioxolan-4-yl)-methyl (meth)acrylate, cyclohexanespiro-2-(1,3-dioxolan-4-yl)-methyl (meth)acrylate, 3-ethyl-3-oxetanylmethyl (meth)acrylate, γ-butyrolactone (meth)acrylate, n-butyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, dodecyl (meth)acrylate, n-stearyl (meth)acrylate, benzyl (meth)acrylate, phenol ethylene oxide modified (n=2) (meth)acrylate, nonylphenol propylene oxide modified (n=2.5) (Meth)acrylate, half (meth)acrylate of phthalic acid derivative such as 2-(meth)acryloyloxyethyl acid phosphate, 2-(meth)acryloyloxy-2-hydroxypropyl phthalate, furfuryl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, carbitol (meth)acrylate, benzyl (meth)acrylate, butoxyethyl (meth)acrylate, allyl (meth)acrylate, (meth)acryloylmorpholine, polyoxyethylene secondary alkyl ether acrylate, and other (meth)acrylate monomers, 2-hydroxyethylacrylamide, N-methylol (meth)acrylamide, N-vinylpyrrolidone, 2-vinylpyridine, vinyl acetate, and the like. In addition, n in the above compound names represents the average number of moles of alkylene oxide added.

[0087] [Multifunctional (meth)acrylate] Examples of the polyfunctional (meth)acrylate include difunctional (meth)acrylate and trifunctional or higher (meth)acrylate. Examples of bifunctional (meth)acrylates include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethylene oxide modified bisphenol A type di(meth)acrylate, propylene oxide modified bisphenol A type di(meth)acrylate, cyclohexanedimethanol di(meth)acrylate, ethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, propylene oxide modified bisphenol A type di(meth)acrylate, cyclohexanedimethanol di(meth)acrylate, ethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, propylene oxide modified bisphenol A type di(meth)acrylate, cyclohexanedimethanol di(meth)acrylate, dipropylene glycol di(meth)acrylate, propylene glycol ... propylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate Examples of the di(meth)acrylate include acrylate, ethoxylated cyclohexane dimethanol di(meth)acrylate, dimethylol dicyclopentane di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, glycerin di(meth)acrylate, pentaerythritol di(meth)acrylate, ethylene glycol diglycidyl ether di(meth)acrylate, diethylene glycol diglycidyl ether di(meth)acrylate, phthalic acid diglycidyl ester di(meth)acrylate, hydroxypivalic acid modified neopentyl glycol di(meth)acrylate, and isocyanuric acid ethylene oxide modified diacrylate.

[0088] Examples of the trifunctional or higher acrylates include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tri(meth)acryloyloxyethoxytrimethylolpropane, glycerin polyglycidyl ether poly(meth)acrylate, isocyanuric acid ethylene oxide modified triacrylate, caprolactone modified dipentaerythritol penta(meth)acrylate, caprylic acid ethylene oxide ... Examples of the ethylene oxide modified dipentaerythritol hexa(meth)acrylate include lactone-modified dipentaerythritol hexa(meth)acrylate, caprolactone-modified pentaerythritol tri(meth)acrylate, caprolactone-modified pentaerythritol tetra(meth)acrylate, ethylene oxide-modified dipentaerythritol penta(meth)acrylate, ethylene oxide-modified dipentaerythritol hexa(meth)acrylate, ethylene oxide-modified pentaerythritol tri(meth)acrylate, ethylene oxide-modified pentaerythritol tetra(meth)acrylate, and ethoxylated 15 glycerin triacrylate.

[0089] The active energy ray-curable compound (B) may also contain, as another constituent compound, a Michael adduct of acrylic acid or a 2-acryloyloxyethyl dicarboxylate monoester. Examples of the Michael adduct of acrylic acid include (meth)acrylic acid dimer, (meth)acrylic acid trimer, and (meth)acrylic acid tetramer. The 2-acryloyloxyethyl dicarboxylate monoester is a carboxylic acid having a specific substituent, and examples thereof include 2-acryloyloxyethyl succinate monoester, 2-methacryloyloxyethyl succinate monoester, 2-acryloyloxyethyl phthalate monoester, 2-methacryloyloxyethyl phthalate monoester, 2-acryloyloxyethyl hexahydrophthalate monoester, and 2-methacryloyloxyethyl hexahydrophthalate monoester. Further examples of other constituent compounds include oligoester acrylates.

[0090] These monofunctional (meth)acrylates, polyfunctional (meth)acrylates and other constituent compounds can be used alone or in combination of two or more.

[0091] The content of the urethane (meth)acrylate compound (b) in the active energy ray curable compound (B) is usually 50% by weight or more, preferably 80% by weight or more, with the upper limit being 100% by weight. If the content is too low, the peelability and stain resistance after irradiation with active energy rays tend to decrease.

[0092] The solvent content in the active energy ray-curable compound (B) is preferably less than 1% by weight, more preferably 0.5% by weight or less, and particularly preferably 0.1% by weight or less. If the content is too high, the cohesive strength of the resulting adhesive layer decreases, and the adhesive performance and releasability before curing with active energy rays tend to decrease. The solvent content was measured by gas chromatography-mass spectrometry (GC-MS).

[0093] [Active energy ray-curable composition (X)] The active energy ray curable composition (X) contains a (meth)acrylic resin (A) and an active energy ray curable compound (B). The content of the active energy ray curable compound (B) is usually 10 to 200 parts by weight, preferably 30 to 150 parts by weight, and more preferably 50 to 120 parts by weight, based on 100 parts by weight of the (meth)acrylic resin (A). If the content of the active energy ray curable compound (B) is too low, the peelability after irradiation with active energy rays tends to be easily reduced, while if it is too high, the cohesive force of the adhesive layer tends to decrease, and the adhesive properties before and after irradiation with active energy rays tend to decrease.

[0094] The requirement (α) of the present invention is that the solvent content in the active energy ray-curable composition (X) is less than 1% by weight, and the solvent content is preferably 0.5% by weight or less, and more preferably 0.1% by weight or less. If the content is too high, the cohesive strength of the resulting adhesive layer decreases, and the adhesive performance and releasability before curing with active energy rays tend to decrease. The solvent content was measured by gas chromatography-mass spectrometry (GC-MS).

[0095] The content of the thermal polymerization initiator in the active energy ray-curable composition (X) is preferably less than 200 ppm, more preferably less than 100 ppm, and particularly preferably less than 50 ppm. If the content is too large, the thermal stability tends to decrease. The content can be reduced by decreasing the content of the thermal polymerization initiator in the (meth)acrylic resin (A). The content of the thermal polymerization initiator is measured by liquid chromatography-mass spectrometry (LC-MS).

[0096] Furthermore, the melt viscosity of the active energy ray-curable composition (X) at 100° C. is preferably 120 Pa·s or less, and more preferably less than 100 Pa·s. If the melt viscosity is too high, the coatability tends to decrease significantly. The melt viscosity of the active energy ray-curable composition (X) at 100° C. is measured by a B-type rotational viscometer.

[0097] [Crosslinker (C)] The active energy ray-curable pressure-sensitive adhesive composition of the present invention contains at least the active energy ray-curable composition (X), and may further contain a crosslinking agent (C). Examples of the crosslinking agent (C) include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, aziridine-based crosslinking agents, oxazoline-based crosslinking agents, melamine-based crosslinking agents, aldehyde-based crosslinking agents, and amine-based crosslinking agents. Among these, it is preferable to use an isocyanate-based crosslinking agent in terms of improving the adhesion of the peel-off pressure-sensitive adhesive sheet to the substrate sheet and in terms of reactivity with the (meth)acrylic resin (A). These crosslinking agents (C) can be used alone or in combination of two or more.

[0098] Examples of the isocyanate-based crosslinking agent include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, hydrogenated tolylene diisocyanate, hydrogenated xylylene diisocyanate, hexamethylene diisocyanate, diphenylmethane-4,4-diisocyanate, isophorone diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, tetramethylxylylene diisocyanate, 1,5-naphthalene diisocyanate, triphenylmethane triisocyanate, and adducts of these polyisocyanate compounds with polyol compounds such as trimethylolpropane, biuret compounds and isocyanurates of these polyisocyanate compounds, and the like. Among these, in terms of chemical resistance and reactivity with functional groups, an isocyanurate of hexamethylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, an adduct of 2,6-tolylene diisocyanate and trimethylolpropane, an isocyanurate of 2,4-tolylene diisocyanate and 2,6-tolylene diisocyanate, and an adduct of tetramethylxylylene diisocyanate and trimethylolpropane are preferred.

[0099] Examples of the epoxy crosslinking agent include bisphenol A-epichlorohydrin type epoxy resins, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl erythritol, diglycerol polyglycidyl ether, 1,3'-bis(N,N-diglycidylaminomethyl)cyclohexane, and N,N,N',N'-tetraglycidyl-m-xylylenediamine.

[0100] Examples of the aziridine crosslinking agent include tetramethylolmethane-tri-β-aziridinylpropionate, trimethylolpropane-tri-β-aziridinylpropionate, N,N'-diphenylmethane-4,4'-bis(1-aziridinecarboxamide), and N,N'-hexamethylene-1,6-bis(1-aziridinecarboxamide).

[0101] Examples of the oxazoline crosslinking agent include 2,2' and bisoxazoline compounds containing aliphatic or aromatic groups such as 1,2-bis(2-oxazoline), 1,2-bis(2-oxazoline-2-yl)ethane, 1,4-bis(2-oxazoline-2-yl)butane, 1,8-bis(2-oxazoline-2-yl)butane, 1,4-bis(2-oxazoline-2-yl)cyclohexane, 1,2-bis(2-oxazoline-2-yl)benzene, and 1,3-bis(2-oxazoline-2-yl)benzene; and polymers of one or more types of addition-polymerizable oxazolines such as 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, and 2-isopropenyl-5-ethyl-2-oxazoline.

[0102] Examples of the melamine-based crosslinking agent include hexamethoxymethylmelamine, hexaethoxymethylmelamine, hexapropoxymethylmelamine, hexaptoxymethylmelamine, hexapentyloxymethylmelamine, hexahexyloxymethylmelamine, melamine resins, and the like.

[0103] Examples of the aldehyde crosslinking agent include glyoxal, malondialdehyde, succindialdehyde, maleic dialdehyde, glutaric dialdehyde, formaldehyde, acetaldehyde, and benzaldehyde.

[0104] Examples of the amine-based crosslinking agent include hexamethylenediamine, triethyldiamine, polyethyleneimine, hexamethylenetetraamine, diethylenetriamine, triethyltetraamine, isophoronediamine, amino resins, and polyamides.

[0105] When the active energy ray-curable adhesive composition of the present invention further contains a crosslinking agent (C), the content of the crosslinking agent (C) is usually preferably 0.1 to 30 parts by weight, more preferably 0.2 to 20 parts by weight, and particularly preferably 0.3 to 15 parts by weight, based on 100 parts by weight of the (meth)acrylic resin (A). If the content of the crosslinking agent (C) is within the above range, the cohesive force of the adhesive layer is further improved, the adhesive properties are good, and the adhesive strength before the active energy ray irradiation is good, so that lifting or peeling tends to be less likely to occur between the adhesive layer and the adherend such as the workpiece.

[0106] [Photopolymerization initiator (D)] The active energy ray-curable pressure-sensitive adhesive composition of the present invention may further contain a photopolymerization initiator (D). The photopolymerization initiator (D) used in the present invention may be any one that generates radicals by the action of light. When the (meth)acrylic resin (A) contains a photocrosslinkable monomer, the (meth)acrylic resin (A) does not need to contain a photopolymerization initiator.

[0107] Examples of the photopolymerization initiator (D) include diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, benzyl dimethyl ketal, 4-(2-hydroxyethoxy)phenyl-(2-hydroxy-2-propyl)ketone, 1-hydroxycyclohexyl phenyl ketone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-methyl-2-morpholino(4-thiomethylphenyl)propanone, and the like. Acetophenones such as Pan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, and 2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone oligomer; benzoins such as benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether; benzophenone, o-benzoylbenzoic acid methyl, 4-phenylbenzophenone, 4-benzoyl-4'-methyl-diphenyl sulfide, 3,3',4,4' -Tetra(tert-butylperoxycarbonyl)benzophenone, 2,4,6-trimethylbenzophenone, 4-benzoyl-N,N-dimethyl-N-[2-(1-oxo-2-propenyloxy)ethyl]benzenemethanaminium bromide, (4-benzoylbenzyl)trimethylammonium chloride and other benzophenones; 2-isopropylthioxanthone, 4-isopropylthioxanthone, 2,4-diethylthioxanthone, 2,4-dichlorothioxanthone, 1-chloro- Thioxanthones such as 4-propoxythioxanthone and 2-(3-dimethylamino-2-hydroxy)-3,4-dimethyl-9H-thioxanthone-9-one mesochloride; and acylphosphine oxides such as 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide. Among these, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, and the like are preferred because they do not sublime even when heated and are stable. These photopolymerization initiators (D) can be used alone or in combination of two or more.

[0108] In addition, as an auxiliary for these photopolymerization initiators (D), it is also possible to use, for example, triethanolamine, triisopropanolamine, 4,4'-dimethylaminobenzophenone (Michler's ketone), 4,4'-diethylaminobenzophenone, 2-dimethylaminoethylbenzoic acid, ethyl 4-dimethylaminobenzoate, (n-butoxy)ethyl 4-dimethylaminobenzoate, isoamyl 4-dimethylaminobenzoate, 2-ethylhexyl 4-dimethylaminobenzoate, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, etc. These auxiliary agents may be used alone or in combination of two or more.

[0109] When the active energy ray-curable pressure-sensitive adhesive composition of the present invention further contains a photopolymerization initiator (D), the content of the photopolymerization initiator (D) is preferably 0.1 to 20 parts by weight, more preferably 0.5 to 15 parts by weight, and particularly preferably 1 to 10 parts by weight, based on 100 parts by weight of the active energy ray-curable compound (B). If the content of the photopolymerization initiator (D) is within the above range, the peelability after irradiation with active energy rays and the contamination resistance of the adherend such as a processed member tend to be further improved.

[0110] [Other ingredients] The active energy ray-curable pressure-sensitive adhesive composition of the present invention may further contain additives such as small amounts of monofunctional monomers, antistatic agents, antioxidants, plasticizers, fillers, pigments, diluents, antioxidants, ultraviolet absorbers, and ultraviolet stabilizers, within the range that does not impair the effects of the present invention. These additives may be used alone or in combination of two or more. In particular, the antioxidant is effective in maintaining the stability of the adhesive layer. When an antioxidant is added, its content is not particularly limited, but is preferably 0.01 to 5% by weight based on the active energy ray-curable adhesive composition. In addition to the above-mentioned additives, the active energy ray-curable pressure-sensitive adhesive composition of the present invention may contain small amounts of impurities contained in the production raw materials of the components of the active energy ray-curable pressure-sensitive adhesive composition.

[0111] In addition, since the pressure-sensitive adhesive composition of the present invention may have reduced contamination resistance to an adherend such as a workpiece after irradiation with active energy rays, it is preferable that the pressure-sensitive adhesive composition of the present invention does not contain a tackifying resin such as a terpene-based resin, a rosin-based resin, a chroman-based resin, a phenol-based resin, a styrene-based resin, or a petroleum-based resin.

[0112] [Active energy ray-curable adhesive composition] Thus, the active energy ray-curable pressure-sensitive adhesive composition of the present invention can be obtained by containing at least the active energy ray-curable composition (X) and, if necessary, further containing optional components such as a crosslinking agent (C), a photopolymerization initiator (D), and other components.

[0113] The solvent content in the active energy ray-curable pressure-sensitive adhesive composition is preferably less than 1.5% by weight, and more preferably less than 1% by weight. If the solvent content is too high, a large amount of the solvent remains in the pressure-sensitive adhesive layer, which tends to reduce the cohesive strength and adhesive properties. The solvent content is measured by gas chromatography-mass spectrometry (GC-MS).

[0114] The active energy ray curable adhesive composition of the present invention can be crosslinked by the above-mentioned crosslinking agent (C) to become a peelable adhesive, and is therefore suitable for use as an adhesive layer of a peelable adhesive sheet. By laminating this peelable adhesive sheet to a workpiece and then irradiating it with active energy rays, the active energy ray curable composition (X) in the adhesive layer is polymerized, the adhesive layer is cured, and the adhesive strength is reduced, resulting in the release of the adhesive. Taking advantage of this characteristic, the peelable adhesive sheet is used to temporarily protect the surface of various workpieces when processing the workpieces. Hereinafter, the peelable pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer in which the active energy ray-curable pressure-sensitive adhesive composition of the present invention is crosslinked will be described.

[0115] [Removable adhesive sheet] The peel-off pressure-sensitive adhesive sheet of the present invention is attached to an adherend such as a workpiece, and then irradiated with active energy rays to harden the pressure-sensitive adhesive layer and reduce the adhesive strength of the pressure-sensitive adhesive layer, thereby making it easier to peel off from the adherend.

[0116] Examples of workpieces that can be protected by the peelable pressure-sensitive adhesive sheet include semiconductor wafers, printed circuit boards, processed glass products, metal plates, and plastic plates.

[0117] The peelable pressure-sensitive adhesive sheet generally comprises a substrate sheet, a pressure-sensitive adhesive layer containing the active energy ray-curable pressure-sensitive adhesive composition of the present invention, and a release film. A method for producing such a peelable adhesive sheet will be briefly described. First, the active energy ray curable adhesive composition of the present invention is applied directly onto a release film or a substrate sheet, either as is or after adjusting the concentration with an appropriate organic solvent. Then, for example, it is dried by heating at 80 to 105°C for 0.5 to 10 minutes, and the resulting composition is attached to a substrate sheet or a release film to obtain a peelable adhesive sheet. In order to balance the adhesive properties, aging may be further performed after drying.

[0118] Examples of the base sheet include polyester-based resins such as polyethylene naphthalate, polyethylene terephthalate, polybutylene terephthalate, and polyethylene terephthalate / isophthalate copolymers; polyolefin-based resins such as polyethylene, polypropylene, and polymethylpentene; polyethylene fluoride resins such as polyvinyl fluoride, polyvinylidene fluoride, and polyethylene fluoride; polyamides such as nylon 6 and nylon 6,6; vinyl polymers such as polyvinyl chloride, polyvinyl chloride / vinyl acetate copolymer, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, polyvinyl alcohol, and vinylon; cellulose-based resins such as cellulose triacetate and cellophane; acrylic resins such as polymethyl methacrylate, polyethyl methacrylate, polyethyl acrylate, and polybutyl acrylate; polystyrene; polycarbonate; polyarylate; and polyimide; metal foils of aluminum, copper, and iron; paper such as fine paper and glassine paper; woven fabrics and nonwoven fabrics made of glass fiber, natural fibers, synthetic fibers, and the like. These substrate sheets can be used as a single layer or as a multi-layered body in which two or more types are laminated. Among these, sheets made of synthetic resins are preferred from the viewpoint of weight reduction, etc.

[0119] As the release film, for example, sheets made of various synthetic resins exemplified above as the base sheet; or sheets of paper, woven fabric, nonwoven fabric, etc., whose surfaces have been subjected to a release treatment, can be used.

[0120] As a method for applying the active energy ray-curable pressure-sensitive adhesive composition, a general application method can be adopted, and examples thereof include roll coating, die coating, gravure coating, comma coating, and screen printing. When the active energy ray-curable pressure-sensitive adhesive composition is dissolved or dispersed in a suitable organic solvent, the organic solvents described in the above section [Production method of (meth)acrylic resin (A)] can be used, and it is preferable to use an organic solvent having a boiling point of 80°C or lower.

[0121] The thickness of the pressure-sensitive adhesive layer in the peelable pressure-sensitive adhesive sheet is preferably from 1 to 200 μm, and more preferably from 10 to 100 μm.

[0122] As the active energy ray, generally, light rays such as far ultraviolet rays, ultraviolet rays, near ultraviolet rays, infrared rays, electromagnetic waves such as X-rays and gamma rays, as well as electron beams, proton beams, neutron beams, etc. can be used. From the viewpoints of curing speed, availability of irradiation equipment, cost, etc., it is advantageous to use ultraviolet rays.

[0123] The cumulative dose of ultraviolet light is usually 50 to 3000 mJ / cm 2 , preferably 100 to 1000 mJ / cm 2 The irradiation time varies depending on the type of light source, the distance between the light source and the adhesive layer, the thickness of the adhesive layer, and other conditions, but is usually several seconds, and in some cases may be a very short time of less than one second.

[0124] The adhesive strength of the peelable adhesive sheet varies depending on the adhesive composition, the type of base sheet, the type of workpiece, etc., but the 180-degree peel strength before irradiation with active energy rays is usually 1 N / 25 mm or more, and preferably 3 N / 25 mm or more.

[0125] The peel strength of the peel-off pressure-sensitive adhesive sheet described above is usually lower after irradiation with active energy rays than before irradiation with active energy rays. The 180 degree peel strength of the above-mentioned peel-type pressure-sensitive adhesive sheet after irradiation with active energy rays is usually less than 1 N / 25 mm, and preferably 0.5 N / 25 mm or less. The 180-degree peel strength in the present invention is measured by the method described in the Examples.

[0126] The peelable adhesive sheet having an adhesive layer crosslinked with the active energy ray-curable adhesive composition of the present invention can temporarily protect the surface of a workpiece by laminating it to the surface of the workpiece, which is the adherend, after peeling off a release film if the peelable adhesive sheet has a release film. In addition, the adhesive layer of the peelable adhesive sheet is cured by irradiation with active energy rays, and the adhesive strength is reduced, so that the peelable adhesive sheet can be easily peeled off from the workpiece. The peelable pressure-sensitive adhesive sheet of the present invention is not limited to a sheet, but may be in a roll, or may be processed into various shapes. A roll-shaped peelable pressure-sensitive adhesive sheet may not have a release film, and in this case, it is preferable that the back surface of the base sheet (the surface opposite to the pressure-sensitive adhesive layer) is release-treated. EXAMPLES

[0127] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention. In the following, "%" and "parts" refer to weight standards. The glass transition temperature (Tg), weight average molecular weight (Mw), solvent content, and melt viscosity (Pa·s (100°C)) are values ​​measured according to the method described in this specification. The viscosity (Pa·s (25°C)) is a value measured using a B-type rotational viscometer.

[0128] <Preparation of (meth)acrylic resin (A) solution> [Acrylic resin (A-1)] Into a reactor equipped with a temperature controller, a thermometer, a stirrer, a dropping funnel and a reflux condenser, 50 parts of methyl ethyl ketone and 0.042 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) (ADVN (thermal polymerization initiator)) as a polymerization catalyst were charged, and the temperature was raised with stirring. When the internal temperature stabilized at 78°C, a mixture of 65.45 parts of 2-ethylhexyl acrylate (a1), 25.45 parts of 2-hydroxyethyl methacrylate (a2), 9.1 parts of vinyl acetate, 0.083 parts of ADVN and 3.3 parts of methyl ethyl ketone as copolymerization components was added dropwise over 2 hours, and the reaction was carried out under reflux. Next, 3 hours after the start of the reaction, a solution containing 3.3 parts of methyl ethyl ketone and 0.083 parts of ADVN was added, and 4.5 hours after the start of the reaction, a solution containing 3.3 parts of ethyl acetate and 0.083 parts of ADVN was added. The reaction was terminated 7 hours after the start of the reaction to obtain an acrylic resin (A-1) solution. The obtained acrylic resin (A-1) had a glass transition temperature (Tg) of -51.4°C, a resin content in the solution of 62.2%, a viscosity of 1500 mPa·s (25°C), and a weight average molecular weight (Mw) of 122,000. The resulting acrylic resin (A-1) solution was then placed in a flask equipped with a reflux liquid withdrawal tube and heated to 90°C for 1 hour, then the pressure was reduced to 10 kPa and the mixture was maintained at 90°C for 3 hours to distill off the solvent, yielding acrylic resin (A-1) (melt viscosity at 100°C: 120 Pa s).

[0129] <Preparation of active energy ray-curable compound (B)> [Urethane acrylate (B-1)] Into a four-neck flask equipped with a temperature controller, a thermometer, a stirrer, a water-cooled condenser, and a nitrogen gas inlet, 25.9 parts of isophorone diisocyanate (isocyanate group content: 37.8%) (manufactured by Evonik Japan Co., Ltd.), 54.9 parts of pentaerythritol triacrylate and pentaerythritol tetraacrylate (hydroxyl value: 119.1 mg KOH / g), 19.2 parts of decyl alcohol (hydroxyl value: 350.9 mg KOH / g) (Kalcol 1098, manufactured by Kao Corporation), and polymerization inhibitor 0.04 parts of 2,6-di-tert-butylcresol as a blocking agent and 0.02 parts of dibutyltin dilaurate, a tin compound, as a reaction catalyst were charged and reacted at 60°C. The reaction was terminated when the residual isocyanate group content reached 0.3% or less, yielding a mixture of urethane acrylate (B-1) (urethane acrylate having 3 (meth)acryloyl groups, weight average molecular weight 900, structure of general formula (1), solvent content 0.1% or less, and acryloyl group concentration 5.79 mmol / g).

[0130] [Urethane acrylate (B-2)] Into a four-neck flask equipped with a temperature controller, a thermometer, a stirrer, a water-cooled condenser, and a nitrogen gas inlet, 25.8 parts of dicyclohexylmethane 4,4'-diisocyanate (isocyanate group content: 32%) (manufactured by Evonik Japan Co., Ltd.), 46.2 parts of pentaerythritol triacrylate and pentaerythritol tetraacrylate (hydroxyl value: 119.1 mg KOH / g), and a branched alcohol having 17 carbon atoms (hydroxyl value: 203 mg KOH / g) (Fine Oxocol 180T, manufactured by Nissan Chemical Co., Ltd.) were added. 28 parts of ethyl acetate, 0.04 parts of 2,6-di-tert-butylcresol as a polymerization inhibitor, and 0.02 parts of dibutyltin dilaurate, a tin compound, as a reaction catalyst were charged and reacted at 60°C. The reaction was terminated when the residual isocyanate group content reached 0.3% or less, yielding a mixture of urethane acrylate (B-2) (urethane acrylate having 3 (meth)acryloyl groups, weight average molecular weight 1,400, structure of general formula (1), solvent content 0.1% or less, and acryloyl group concentration 4.87 mmol / g).

[0131] [Urethane acrylate (B-3)] Into a four-neck flask equipped with a temperature controller, a thermometer, a stirrer, a water-cooled condenser, and a nitrogen gas inlet, 9.4 parts of isophorone diisocyanate (isocyanate group content: 37.8%) (manufactured by Evonik Japan Co., Ltd.), 43.3 parts of polypropylene glycol (hydroxyl value: 54.9 mg KOH / g) (Sanix PP-2000, manufactured by Sanyo Chemical Industries Co., Ltd.), 47.3 parts of a mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (hydroxyl value: 51 mg KOH / g) were added. parts of ethyl acetate, 0.04 parts of 2,6-di-tert-butylcresol as a polymerization inhibitor, and 0.02 parts of dibutyltin dilaurate, a tin compound, as a reaction catalyst were charged and reacted at 60°C. The reaction was terminated when the residual isocyanate group content became 0.3% or less, thereby obtaining a mixture of urethane acrylate (B-3) (urethane acrylate having 10 (meth)acryloyl groups, weight average molecular weight 7,500, and a structure derived from polyol, solvent content 0.1% or less, acryloyl group concentration 4.73 mmol / g).

[0132] [Urethane acrylate (B-4)] Into a four-neck flask equipped with a temperature controller, a thermometer, a stirrer, a water-cooled condenser, and a nitrogen gas inlet, 12.0 parts of hexamethylene diisocyanate (isocyanate group content: 50%) (manufactured by Asahi Kasei Co., Ltd.), 36.1 parts of polypropylene glycol (hydroxyl value: 111 mgKOH / g) (Sannix PP-1000, manufactured by Sanyo Chemical Industries, Ltd.), 41.7 parts of a mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (hydroxyl value: 48 mgKOH / g), and a branched alcohol having a carbon number of 17 (Fine Oxocol 180T, manufactured by Japan Chemical Industry Co., Ltd.) were added. 10.2 parts of 1,2-diphenyl ether (hydroxyl value: 203 mg KOH / g, manufactured by Sankagaku Co., Ltd.), 0.04 parts of 2,6-di-tert-butylcresol as a polymerization inhibitor, and 0.02 parts of dibutyltin dilaurate, a tin compound, as a reaction catalyst were charged and reacted at 60°C. The reaction was terminated when the residual isocyanate group content reached 0.3% or less, yielding a mixture of urethane acrylate (B-4) (urethane acrylate having 5 (meth)acryloyl groups, weight average molecular weight of 1,600, and a structure derived from polyol, solvent content of 0.1% or less, and acryloyl group concentration of 0.99 mmol / g).

[0133] [Urethane acrylate (B'-1)] Into a four-neck flask equipped with a thermometer, a stirrer, a water-cooled condenser, and a nitrogen gas inlet, 6.6 parts of isophorone diisocyanate (isocyanate group content: 37.8%) (manufactured by Evonik Japan Co., Ltd.), 93.4 parts of a mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (hydroxyl value 48 mgKOH / g), 0.06 parts of 2,6-di-tert-butylcresol as a polymerization inhibitor, and 0.02 parts of dibutyltin dilaurate as a reaction catalyst were charged and reacted at 60°C. The reaction was terminated when the residual isocyanate group content became 0.3% or less, and a mixture of urethane acrylate (B'-1) ((meth)acryloyl group number 10, weight average molecular weight 1270, solvent content 0.1% or less, acryloyl group concentration 9.3 mmol / g) was obtained.

[0134] [Urethane acrylate (B'-2)] Into a four-neck flask equipped with a temperature controller, a thermometer, a stirrer, a water-cooled condenser, and a nitrogen gas inlet, 16.3 parts of isophorone diisocyanate (isocyanate group content: 37.8%) (manufactured by Evonik Japan Co., Ltd.), 75 parts of polypropylene glycol (hydroxyl value: 54.9 mg KOH / g) (Sannix PP-2000, manufactured by Sanyo Chemical Industries, Ltd.), 8.7 parts of 2-hydroxyethyl acrylate (hydroxyl value: 483.2 mg KOH / g), 2,6- 0.04 parts of di-tert-butylcresol and 0.02 parts of dibutyltin dilaurate, a tin compound, as a reaction catalyst were charged and reacted at 60°C. The reaction was terminated when the residual isocyanate group content reached 0.3% or less, yielding a mixture of urethane acrylate (B'-2) (urethane acrylate having two (meth)acryloyl groups, weight average molecular weight of 5,700, and a polyol-derived structure, solvent content of 0.1% or less, and acryloyl group concentration of 0.74 mmol / g).

[0135] [Multifunctional acrylate (B'-3)] Mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (hydroxyl value 48mgKOH / g)

[0136] [Multifunctional acrylate (B'-4)] Trimethylolpropane triacrylate (Aronix M-309, manufactured by Toagosei Co., Ltd.)

[0137] [Active energy ray-curable composition (X)<X-1~4、X’-1~4> Preparation of The acrylic resin (A) and the active energy ray curable compound (B) were mixed in the amounts shown in Table 1 to obtain an active energy ray curable composition (X).<X-1~4、X’-1~4> obtained.

[0138] [Requirement (α): Solvent content (wt%)] The solvent content in the obtained active energy ray-curable composition (X) was measured. The results are shown in Table 1.

[0139] [Requirement (β): Presence or absence of urethane (meth)acrylate in compound (B)] When the active energy ray curable compound (B) used contained the urethane (meth)acrylate (b), it was marked with "○" in Table 1, and when it did not contain the urethane (meth)acrylate (b), it was marked with "×" in Table 1.

[0140] [Requirement (γ): Presence or absence of specific structure of urethane (meth)acrylate (b)] When the urethane (meth)acrylate (b) has the structure shown in general formula (1) and / or a structure derived from a polyol and has three or more (meth)acryloyl groups per molecule, it is marked with "○" in Table 1, and otherwise it is marked with "×" in Table 1. When it does not fall under the category of urethane (meth)acrylate, it is marked with "-" in Table 1.

[0141] [compatibility] The appearance of the obtained active energy ray-curable composition (X) was visually observed and evaluated according to the following criteria. ○: Uniform and transparent △: Uniform and slightly cloudy ×: Non-uniform (separated) or cloudy

[0142] [Melt Viscosity] The obtained active energy ray-curable composition (X) was allowed to stand at 100° C. for 24 hours, and then the viscosity at 100° C. was measured using a B-type rotational viscometer and evaluated according to the following criteria. ○: Melt viscosity 120 Pa s or less ×: Melt viscosity exceeds 120 Pa s

[0143] [Table 1]

[0144] <Examples 1 to 4 and Comparative Examples 1 to 4> The acrylic resin (A), active energy ray curable compound (B) and the following components were mixed in the amounts shown in Table 2 to obtain an active energy ray curable pressure-sensitive adhesive composition. Furthermore, a peel-type pressure-sensitive adhesive sheet was produced using this pressure-sensitive adhesive composition.

[0145] [Crosslinking agent (C)] Isocyanate-based crosslinking agent (C-1): Trimethylolpropane adduct of tolylene diisocyanate (Coronate L-55E, manufactured by Tosoh Corporation)

[0146] [Photopolymerization initiator (D)] Photopolymerization initiator (D-1): 2-dimethylamine-2-(4-methylbenzyl)-1-(4-morpholin-4-yl-phenyl)-butanone (OMNIRAD379, IGM Resins)

[0147] [Preparation of peelable adhesive sheet] The components shown in Table 2 were mixed with the obtained active energy ray-curable adhesive composition, and the temperature was adjusted to 100°C, after which the composition was applied with an applicator onto a polyethylene terephthalate film (film thickness 38 μm) (T60 Lumirror, manufactured by Toray Industries, Inc.) as a substrate sheet. The composition was dried at 100°C for 2 minutes, cooled to room temperature, and then attached to a release film (SP-PET3801-BU, manufactured by Mitsui Chemicals Tocello, Inc.) and aged at 40°C for 7 days to obtain a peelable adhesive sheet (adhesive layer thickness 25 μm). The peelable pressure-sensitive adhesive sheets obtained were subjected to the following evaluations, and the results are shown in Table 2.

[0148] (Adhesive strength before exposure to active energy rays) A 25mm x 100mm test piece was prepared from the peelable adhesive sheet obtained above, and after removing the release film, it was pressed and attached to a stainless steel plate (SUS304BA plate) by rolling a 2kg rubber roller back and forth twice in an atmosphere of 23°C and 50% relative humidity. After leaving it to stand for 30 minutes in the same atmosphere, the 180° peel strength (N / 25mm) was measured at a peel speed of 300mm / min and evaluated according to the following criteria. ○:5N / 25mm or more △: 1N / 25mm or more, less than 5N / 25mm ×: Less than 1N / 25mm

[0149] (Adhesive strength after exposure to active energy rays) A 25mm x 100mm test piece was prepared from the peelable adhesive sheet obtained above, and after removing the release film, it was pressed and attached to a stainless steel plate (SUS304BA plate) by rolling a 2kg rubber roller back and forth twice in an atmosphere of 23°C and 50% relative humidity. After leaving it to stand for 30 minutes in the same atmosphere, it was irradiated with ultraviolet light (cumulative irradiation amount 250mJ / cm2) from a height of 18cm at a conveyor speed of 51m / min using one 80W high-pressure mercury lamp. 2 After leaving the sample to stand for 30 minutes in an atmosphere of 23°C and 50% relative humidity, the 180° peel strength (N / 25 mm) was measured at a peel speed of 300 mm / min and evaluated according to the following criteria. ○: Less than 0.1N / 25mm △: 0.1N / 25mm or more, less than 1.0N / 25mm ×:1.0N / 25mm or more

[0150] [Table 2]

[0151] The active energy ray-curable compositions (X-1 to 4) shown in Table 1 have good or excellent compatibility between the acrylic resin (A) and the active energy ray-curable compound (B), and the peelable pressure-sensitive adhesive sheets of Examples 1 to 4 obtained using these compositions (X-1 to 4) also had excellent adhesive strength before and after exposure to active energy rays. On the other hand, in Comparative Example 1, in which the active energy ray-curable compound (B) was a urethane acrylate (B'-1) not containing general formula (1) and / or a polyol structure, and in Comparative Example 3, in which a mixture (B'-3) of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate was used as the active energy ray-curable compound (B), compatibility with the acrylic resin (A) was poor, so a peel-off adhesive sheet could not be obtained. In addition, the active energy ray-curable composition (X'-2) using a urethane acrylate (B'-2) having only two acryloyl groups as the active energy ray-curable compound (B) had excellent compatibility and melt viscosity, but the peelable adhesive sheet of Comparative Example 2 obtained using this composition (X'-2) had poor adhesive strength after curing with active energy rays. Furthermore, the active energy ray-curable composition (X'-4) using trimethylolpropane triacrylate (B'-4) as the active energy ray-curable compound (B) also had excellent compatibility and melt viscosity, and the peel-type adhesive sheet of Comparative Example 4 obtained using this composition (X'-4) had excellent adhesive strength after exposure to active energy rays, but had inferior adhesive strength before curing with active energy rays.

[0152] From the above results, it is found that the active energy ray curable compound (B) contains urethane (meth)acrylate (b), and the urethane (meth)acrylate (b) has the structure described in general formula (1) and / or a structure derived from a polyol, and has three or more (meth)acryloyl groups per molecule, so that it has excellent compatibility with the acrylic resin (A) and melt viscosity. In addition, it is found that when a peelable adhesive sheet is produced using this composition, it has excellent adhesive strength before and after irradiation with active energy rays, as well as excellent stain resistance and peelability after peeling. [Industrial Applicability]

[0153] The active energy ray-curable pressure-sensitive adhesive composition of the present invention can be suitably used as a pressure-sensitive adhesive sheet for temporary surface protection when processing semiconductor wafers, printed circuit boards, processed glass products, metal plates, plastic plates, and the like.

Claims

1. An active energy ray-curable pressure-sensitive adhesive composition comprising at least an active energy ray-curable composition (X) containing a (meth)acrylic resin (A) and an active energy ray-curable compound (B), and satisfying all of the following requirements (α), (β), and (γ): Requirement (α): The solvent content in the active energy ray-curable composition (X) is less than 1% by weight. Requirement (β): The active energy ray-curable compound (B) contains a urethane (meth)acrylate (b). Requirement (γ): The urethane (meth)acrylate (b) has a structure represented by general formula (1) and / or a structure derived from a polyol, and has three or more (meth)acryloyl groups per molecule. -UA General formula (1) [U represents a urethane bond, and A represents at least one selected from a linear or branched alkyl group, an alicyclic structure, an aromatic ring structure, and a heterocyclic structure.]

2. 2. The active energy ray-curable pressure-sensitive adhesive composition according to claim 1, wherein the active energy ray-curable composition (X) has a melt viscosity at 100°C of 120 Pa·s or less.

3. 3. The active energy ray-curable pressure-sensitive adhesive composition according to claim 1, wherein the urethane (meth)acrylate (b) has at least one structural unit selected from the group consisting of isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, and hexamethylene diisocyanate.

4. The active energy ray-curable pressure-sensitive adhesive composition according to any one of claims 1 to 3, further comprising a crosslinking agent (C).

5. The active energy ray-curable pressure-sensitive adhesive composition according to any one of claims 1 to 4, further comprising a photopolymerization initiator (D).

6. A peelable pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer in which the active energy ray-curable pressure-sensitive adhesive composition according to any one of claims 1 to 5 is crosslinked.

Citation Information

Patent Citations

  • Hot-melt pressure-sensitive adhesive composition curable by actinic radiation

    JP1991115481A

  • Production of sticky article

    JP1994336583A

  • Pressure sensitive adhesive sheet for use in semiconductor wafer processing and its manufacturing method

    JP2004269796A

  • Adhesive, and adhesive sheet using the same, temporarily surface-protecting adhesive, and temporarily surface-protecting adhesive sheet using the same, method of using the temporarily surface-protecting sheet, and active energy ray-curable resin composition

    JP2009287016A

  • Emulsion type adhesive composition, adhesive sheet, and method of removing the adhesive sheet

    JP2012001615A